Atomic grammar: a learning source of ESL error identification and correction / Nor Syamimi Iliani Che Hassan ... [et al.] - Che Hassan, Nor Syamimi Iliani; Mohammad Nor, Nor Hairunnisa; Wan Zakaria, Wan Nuur Fazliza; Rosly, Rohazlyn (Universiti Teknologi MARA, 2020)
Error analysis is deemed a fundamental component in language teaching which helps language learners to identify, understand and eventually correct language errors on their own. 40 ESL students took part in the study by producing two sets of 100-word composition. The researchers identified the grammatical errors in the essays before performing error analysis and error correction on the identified errors. The findings were utilized for the construction of Atomic Grammar, an online source of English language grammar lessons based on error identification and error correction. The website which is accessible via personal computers and smartphones stores a compilation of the common errors made by ESL learners in their compositions followed by detailed explanation which include the reasons and rules that formulate the correct use of English parts of speech. In short, Atomic Grammar offers benefits to both language learners and instructors at all levels of English language competency.